Altruism and community resilience: integrating indigenous wisdom systems in mount merapi volcanic disaster management - Rasidi Rasidi; Galih Istiningsih; Robiul Fitri Masithoh; M Imron Rosyidi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This ethnographic study examines how altruism, institutionalized through indigenous wisdom systems, enhances community resilience in four Merapi slope villages. Through interviews with 28 key informants (traditional leaders, religious figures, disaster survivors, and volunteers), focus group discussions, and participant observation, data were analyzed using thematic analysis. Results reveal that gotong royong (mutual cooperation) emerged as the dominant resilience mechanism, mentioned by 96.4% of participants, with 82.1% identifying it as the primary factor. However, effectiveness requires integration with leadership structures (89.3% mentioned as critical), resource accessibility (85.7%), and institutional support (71.4%). Cultural values gotong royong and tepo seliro(empathetic consideration) serve as foundations for social bonding that facilitate post-disaster recovery. Traditional ecological knowledge, comprising 23 environmental indicators, showed 67% correlation with seismographic data and provided 18–36 hour early warning advantages over official evacuation notices. Yet systematic challenges constrain cooperation effectiveness: internal conflicts (28.6% of cases), resource limitations (64.3%), and bureaucratic coordination delays (averaging 2.3 days). Villages with strong cooperation but weak institutional linkages experienced 6-hour evacuation delays and 40% higher resource consumption compared to integrated systems. The study concludes that altruism-based resilience operates through multi-factorial mechanisms rather than cooperation alone. Practical recommendations include integrating traditional early warning systems into village disaster policies through hybrid monitoring protocols, establishing community liaison roles, and implementing leadership training programs combining cultural values with modern coordination mechanisms.